(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: to present a reflection on the perception of patients living with intestinal stomas in the light of phenomenology, presenting Merleau-Ponty’s assumptions as a philosophical basis. Method: this is a reflective study based on the philosophical theoretical basis of phenomenology, presenting findings in the literature and the author’s view on the topic addressed. Results: perception isn’t simply the thing visible to the eye, but it has a meaning in relation to the subjective interpretation of the observer, with the body as the center of observation. People with ostomies have an individual perception of the changes that the ostomy can bring to their lives, and in this aspect we can make a connection with Merleau’s thoughts, in which the perception of the body and the being it presents itself in a particular way from the perspective of the observer. Conclusion: This reflection enabled a better perception of patients living with intestinal ostomies, presenting, for each situation they experience, a positive or negative emotion, as a reflection of the body and mind relationship, enabled the understanding of the vision of people with ostomies before of the lived experiences from the corporal change based on the phenomenology of Merleau-Ponty’s thoughts.